Pengaruh Service Innovation dan E-Service Quality terhadap Loyalitas Nasabah pada Bank Muamalat KC Sumber: The Influence of Service Innovation and E-Service Quality on Customer Loyalty at Bank Muamalat KC Sumber - Atiatul Maollah; Refaldo Fanther; Rita Kusumadewi (Jurnal Keuangan dan Perbankan Syariah, 2026)
Purpose: This study aims to analyze and measure the effect of Service Innovation and E-Service Quality on customer loyalty at Bank Muamalat KC Sumber. Design/methodology/approach: This research uses a quantitative approach with survey design, involving 100 customer respondents. Data were analyzed using PLS-SEM to test the relationships between the variables. Research Findings: The results indicate that both Service Innovation (X1) and E-Service Quality (X2) have a positive and significant effect on customer loyalty (Y). Simultaneously, X1 and X2 explain 83% of the variance in customer loyalty, while the remaining 17% is influenced by other factors outside this study. Contribution/Originality/Novelty: This study contributes to the literature on Islamic banking by highlighting the importance of service innovation and digital service quality in building customer loyalty. It also provides practical implications for bank management in designing service strategies that align with Islamic principles.